(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
This article aims to improve the mechanical properties of the ingot by controlling the cooling process of the ingot by sending air at a certain pressure in addition to the cooling rate during the cooling of gray cast iron melted in an induction furnace in a sand-clay mold